Frequency of metabolic syndrome in students at a Brazilian public university (Research, Society and Development, 2021)
Introduction: Metabolic Syndrome (MS) is characterized by metabolic disorders that generate central obesity, systemic arterial hypertension, dyslipidemia and glucose intolerance. The prevalence of MS among young adults is considered low, however its individual components have been worryingly increasing. The morbidity and mortality rate resulting from chronic diseases among young people is worrying in Brazil and early diagnosis is important because it is a silent syndrome. Objective: To determine the prevalence of MS in university students of a Public Education Institution (IES). Methods: descriptive study, sample composed of 123 university students of both genders, aged between 18 and 22 years. A questionnaire was used for socioeconomic and lifestyle information. Blood collection and anthropometric data were performed at the IES itself. Results: 69.1% were female; 12.2% have had active contact with tobacco; 56.1% consumed alcoholic beverages at least once in the last 30 days; 67.47% were sedentary. 54.28% are overweight; 15.8% of men have a moderately high waist-hip ratio; among women, 44.7% are at moderate risk; 10.6% high risk and 5.9% very high risk ratio. The most altered individual parameter was HDLc 30.9%, while the least altered was blood glucose with 0.81%. Conclusion: despite the low frequency of MS observed in the study, there was a considerable frequency of at least one altered parameter, especially TAG and HDLc, which requires early diagnosis and monitoring to prevent the chronic development of MS.